Endoscopic retrograde appendicitis therapy in the management of chronic fecalith appendicitis in a patient with ulcerative colitis: The first human case report - Zulqarnain, Muhammad; Cui, Guangxing; Lyu, Wen; Huang, Haitao; Wang, Xia; Abdi, Hamse Mohamoud; Gu, Lingfei; Fang, Shijie; Liu, Fangzhou; Ling, Liqian (Frontiers in Immunology, 2023)
To assess the effectiveness of endoscopic retrograde appendicitis therapy (ERAT) as a new technique and method for chronic fecalith appendicitis complicated by active ulcerative colitis. A 46-year-old male patient was admitted with right iliac fossa pain, tenderness, and raised inflammatory markers. A computed tomography (CT) scan of his abdomen confirmed a dilated appendix, which is considered chronic fecalith appendicitis combined with active ulcerative colitis. He was treated with an endoscopic retrograde appendicitis therapy procedure. The patient recovered well after the ERAT procedure and was discharged from the hospital in two days. On follow-up one year later, there was no recurrence of pain in his abdomen. In conclusion, ERAT could be seen as a different approach and be favored as a safer and more effective option in treating UC patients with appendicitis, especially those who are later in the course of the disease. Because of the ERAT procedure, such cases can avoid surgery and surgery-related complications. More research and issues must be addressed to demonstrate the efficacy and effectiveness of ERAT in appendicitis combined with UC.